Pengaruh Kinerja Keuangan Terhadap Laba Per Saham Selama Pandemi Covid-19 - Dili, Bryan Enrique; Laturette, Kazia (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2025)
This research aims to determine the effect of company financial performance such as Current Ratio (CR), Total Asset Turnover (TATO), Net Profit Margin (NPM) and Total Debt to Asset Ratio (TDAR) on Earning Per Share (EPS). The population in this study are property sector companies listed on the Indonesia Stock Exchange in the 2020-2021 period. After carrying out outliers, the research sample obtained during the Covid-19 pandemic was 27 samples of property sector companies listed on the Indonesia Stock Exchange. The results of this research show that the financial performance mechanism consists of Current Ratio (CR), Total Asset Turnover (TATO), Net Profit Margin (NPM) and Total Debt to Asset Ratio (TDAR) which must have a significant value of > 0.05. Based on these results, it can be concluded that the financial performance mechanism consisting of Current Ratio (CR) during the pandemic, Net Profit Margin (NPM) during the pandemic and Total Debt to Asset Ratio (TDAR) during the pandemic did not have a significant effect on Earning Per Share (EPS).